2002
DOI: 10.1046/j.1365-3059.2002.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic structure of Phytophthora infestans populations on potato and tomato in France and Switzerland

Abstract: A total of 134 isolates of Phytophthora infestans were collected from potato and 42 from tomato fields in Switzerland and France in 1996 and, and compared with isolates from other countries. The structure of the populations was analysed phenotypically and genotypically, and associated to geographical, seasonal and host origin. Phenotype characteristics of the isolates included mating type; sensitivity to phenylamide fungicides; virulence on potato differentials; and pathogenic fitness. Genotypes were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
164
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(182 citation statements)
references
References 34 publications
16
164
1
1
Order By: Relevance
“…This finding is in agreement with prior studies by Lebreton and Andrivon (1998), Oyarzun et al (1998), Knapova andGisi (2002), andBland贸n-Diaz et al (2012), and indicates lower host specificity of T isolates than P isolates to a potato host. Cohen (2002) found that P and T isolates collected in Israel between 1998 and 2000, when heavy epidemics of late blight occurred in tomato, had similar complex virulence spectra with unexpectedly high frequencies of the factor against the R9 gene and low frequency of the factor corresponding with R2.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This finding is in agreement with prior studies by Lebreton and Andrivon (1998), Oyarzun et al (1998), Knapova andGisi (2002), andBland贸n-Diaz et al (2012), and indicates lower host specificity of T isolates than P isolates to a potato host. Cohen (2002) found that P and T isolates collected in Israel between 1998 and 2000, when heavy epidemics of late blight occurred in tomato, had similar complex virulence spectra with unexpectedly high frequencies of the factor against the R9 gene and low frequency of the factor corresponding with R2.…”
Section: Discussionsupporting
confidence: 93%
“…The virulence spectra of isolates recently collected from potato in Poland (艢liwka et al 2006;Chmielarz et al 2014) were similar to our results. The frequencies of P isolates that were virulent against respective R-genes in our study were higher than those reported by Andrivon et al (1994), 艢wie偶y艅ski et al (2000), Knapova andGisi (2002), andBland贸n-Diaz et al (2012). On the whole, the P isolates tested in this study showed 100 % of virulent forms against R1, R3, R4, R7, R10, and R11 and frequent presence of virulence against R5, R6, and R8 differentials.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Analysis by RFLP provides greater resolution of P. infestans genotypes with well-characterized markers that are conserved and stringent but it also requires the isolation and propagation of the pathogen, a process that often takes weeks or months to complete (Goodwin et al 1992;Hausner et al 2000). Most recently, analysis of simple sequence repeats (SSRs) has been used to distinguish the P. infestans genotypes (Knapova and Gisi 2002;Lees et al 2006). This PCR-based method may be used on small samples and sporangia from a lesion, and thereby facilitate the rapid identification of a P. infestans genotype (Cooke and Lee 2004;Lees et al 2006;Danies et al 2013).…”
Section: Late Blight Population Genetic Diversitymentioning
confidence: 99%